Changes students' attitudes toward sports and sports activities, and to the assessment of their own health during the period of their studies at the university - Larisa Lutsenko; Anastasija Sutula; Shuteev Vjаcheslav; Nataliya Batieieva; Dmitrii Mel'nichuk (Kharkiv State Academy of Physical Culture, 2014)
Purpose: based on the analysis results of the survey highlight the changing attitudes to sports and sports activities and their health in students of Law University during their university studies. Material and Methods: the study involved students of the first and second courses The Prosecutors' Training Institute and faculty number 9 of the National Law University named after Yaroslav the Wise and students of the Kiev National University of Culture and Arts and Zhytomyr State University named after Ivan Franko. Results: revealed that the overall level of health in students of Law of the University, the highest compared to students studying in several universities not a sports profile. Also confirmed that the period of studies in university students of the law increased interest in physical culture in comparison with students enrolled in other non-core university. Conclusions: this study suggests that during the period of study in law university in the second year compared with the first reduced the number of students who have an interest in physical culture is growing and students assess their health as good. The analyzed data indicate that the period of study at the University of the number of students who engaged in physical activity outside the classroom increases by 12.5%.